2023
DOI: 10.3390/foods12020383
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cheonggukjang (Fermented Soybean) on the Development of Colitis-Associated Colorectal Cancer in Mice

Abstract: Colorectal cancer (CRC) is the third most common type of cancer and is caused by multiple factors. Chronic inflammation, known to cause inflammatory bowel disease (IBD), is closely associated with CRC. Cheonggukjang (CJ), a traditional Korean fermented soybean, is a functional food with anti-inflammatory effects in the intestines, but its anti-cancer effects have not yet been explored. In this study, we investigated the cancer-protective effects of cheonggukjang in an azoxymethane/DSS (AOM/DSS)-induced colitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Cheonggukjang is a traditional Korean fermented soybean that contains significant amounts of γ-PGA. ( 38 ) Administration of cheonggukjang to mice modulated pro-inflammatory and anti-inflammatory cytokine levels via the suppression of NF-κB and inflammatory mediator signaling pathways. ( 38 ) The mRNA levels of anti-inflammatory cytokines ( Il-4 and Il-10 ) in the large intestine of mice were significantly higher in the cheonggukjang group than in the non-administered control group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cheonggukjang is a traditional Korean fermented soybean that contains significant amounts of γ-PGA. ( 38 ) Administration of cheonggukjang to mice modulated pro-inflammatory and anti-inflammatory cytokine levels via the suppression of NF-κB and inflammatory mediator signaling pathways. ( 38 ) The mRNA levels of anti-inflammatory cytokines ( Il-4 and Il-10 ) in the large intestine of mice were significantly higher in the cheonggukjang group than in the non-administered control group.…”
Section: Discussionmentioning
confidence: 99%
“…( 38 ) Administration of cheonggukjang to mice modulated pro-inflammatory and anti-inflammatory cytokine levels via the suppression of NF-κB and inflammatory mediator signaling pathways. ( 38 ) The mRNA levels of anti-inflammatory cytokines ( Il-4 and Il-10 ) in the large intestine of mice were significantly higher in the cheonggukjang group than in the non-administered control group. ( 38 ) Our results showed that the mRNA levels of Il-4 and Il-10 in the large intestine of the NA group tended to be higher than those in the Con group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, despite the regular consumption of traditional fermented products, i.e., Cheonggukjang, no cases of illness or death caused by BA in these fermented foods have been reported. Simultaneously, research continues to produce evidence of the potential health benefits of consuming these traditional fermented foods [21][22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Microbial analysis of Gochujang was measured as previously described using Next-Generation Sequencing (NGS) [ 26 ]. DNA from Gochujang (TCG22-25 and TCG22-48) was extracted using the DNeasy PowerSoil Kit (Qiagen, Germany).…”
Section: Methodsmentioning
confidence: 99%